POSSIBLE CHANGES IN THE CENTRAL HEMODYNAMICS IN PORTAL HYPERTENSION DUE TO LIVER CIRRHOSIS OF VIRAL ETIOLOGY WITH DIFFERENT LEVELS OF CYTOKINES - V. E Kulikov; T. A. Emelina; O. G. Kazakova; K. V. Nikolaevа; M. E. Hapman; M. A. Tonеeva (Рациональная фармакотерапия в кардиологии)
Aim. To study possible variants of changes in structural and functional parameters of central hemodynamics in liver cirrhosis classes A, B, C (Child– Pugh) to improve the early diagnostics of extrahepatic complications.Material and methods. Parameters of central hemodynamics were studied in 107 patients with liver cirrhosis of viral etiology classes A, B, C (ChildPugh) with different levels of serum interleukins (interleukin-2, interleukin-6, tumor necrosis factor alpha).Results. Significant changes in the central hemodynamics parameters were not revealed in liver cirrhosis of classes A and B. In patients with liver cirrhosis of class С the following significant changes of the left and right heart were found: thickening of the interventricular septum and left ventricular posterior wall up to 12.9Ѓ}1.3 and 13.5Ѓ}1.4 mm respectively; increase in left atrium up to 43.1Ѓ}4.7 mm; right ventricular dilatation up to 38.6Ѓ}4.1 mm and pulmonary artery up to 35.7Ѓ}3.1 mm with an increase in pressure in it up to 35.7Ѓ}3.1 mm Hg. The rate and variants of changes in structural and functional parameters of central hemodynamics correlated with the stages of the liver cirrhosis compensation and the interleukins serum levels.Conclusion. Changes in parameters of central hemodynamics in liver cirrhosis depends on the stage of compensation. The most pronounced systolic and diastolic myocardial dysfunctions were observed in cirrhosis Class C, with high levels of portal pressure and high concentrations of serum interleukins. Concentric remodeling of the left ventricular and isolated ventricular septal hypertrophy were the worst types of the left ventricular remodeling. These variants of ventricular geometry were accompanied by the most severe impairments of diastolic function.